Minimally-invasive technologies in the treatment of choledocholithiasis complicated by biliary pancreatitis - Deikalo, I.; Osadchuk, D.; Karel, O.; Handzhalas, M. (Journal of Education, Health and Sport, 2021)
Minimal invasive endoscopic technologies are used in the treatment of patients with biliary pancreatitis with complicated cholangitis and biliary sepsis. 56 patients were treated for the period 2014 - 2018, aged 65.5 ± 15.18 years. ERCP was performed in 31 (55,3%) patients, in 13 (23,2%) - surgical intervention was performed without contrast of extrahepatic bile ducts. Papillotomy in 52 cases (96,4%) was performed by string papilloma and in 4 (7,1%) - by needle. In all cases, subtotal papilloprotectomy was performed [1], supplemented by balloon sphincteroplasty. In the I group, the patients included patients with biliary pancreatitis clinic, in group II patients with clinic of biliary sepsis, in the III group patients with purulent cholangitis clinic, biliary sepsis and septic shock. In the 1st and 2nd groups of patients, mortality was not observed. In the 3rd group, 3 patients died (37,5%). The rest of the patients are discharged from the hospital in a satisfactory condition. A decrease in the level of markers of hepatitis cytolysis (AlAT, AsAT, GGTP, L-FABP) was observed during surgical procedures without ERCP, indicating the toxic effect of contrast on the liver parenchyma. L-FABP is a highly informative marker for hepatocyte cytolysis and can be used as a criterion for hepatic insufficiency and prognosis of biliary sepsis. The high efficiency of transpacillary endoscopic surgical techniques in the treatment of biliary pancreatitis and biliary sepsis was noted.